A communication architecture for spontaneous systems. - Latvakoski, J. (IEEE Wireless communications)
In this article a communication architecture concept for spontaneous systems is provided. The concept integrates application-level spontaneous group communication and ad hoc networking together. A service gateway is applied as a key architecture element to connect multiple technologies and networks together. A set of methods to enable plug and play, addressing and mobility, peer-to-peer connectivity, and use of services is provided. Finally, the provided methods are discussed based on the realized research experiments.